Setting the agenda through Twitter: Assessing news framing of events in Nigeria's 2019 electioneering - Auwal, Ahmad Muhammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Whereas the evolution of interactive media facilitates the rise of user-generated content thus introducing changes into the practices of political communication and journalism at large, only a few studies were conducted to uncover how these developments increasingly influence the news practices of mainstream media. However, little or none of the studies were conducted in the Nigerian context. Accordingly, this study based its construct on the agenda-setting, agenda-building and framing hypotheses to examine how political messages with built-in frames from the Twitter handles of two presidential candidates: Muhamadu Buhari of the APC and Atiku Abubakar of PDP set the news agenda for mainstream media thereby influencing public perceptions about issues in the period of 2019 electioneering in Nigeria. Based on a mixed method of qualitative and quantitative content analysis of n300 tweets from these candidates and n300 news content published via the handles of Daily Trust, Punch and Vanguard newspapers, the study reveals that the mainstream media relied on the tweets as one of their major sources of information about the electioneering activities of the candidates, thus making similar issues become dominant in both the politicians’ agendas and the news agenda of the mainstream media during the period. Besides, the mainstream media contributed meaningfully in emphasizing the narrative frames in the candidates’ agenda through the style of presentation of candidates’ tweets in the news. The study concludes by recommending the need for improved professionalism on the part of journalists and the media, and increased media literacy skills on the part of Nigerian audiences.

ÖZ: Katılımcı platformların evrimi, kullanıcı katkılı içeriğin artmasını kolaylaştırmakta, böylece genel olarak siyasal iletişimin ve gazeteciliğin uygulamasında değişiklikler ortaya koymasına rağmen, söz konusu gelişmelerin ana akım medyadaki haber uygulamaları üzerindeki etkisinin nasıl artış gösterdiği konusuna ışık tutan sadece sayılı miktarda çalışma mevcuttur. Var olan çalışmaların ise çok azı veya hiçbiri, Nijerya bağlamında yer almaktadır. Dolayısıyla söz konusu çalışma, iki başkan adayının (APC’den Muhamadu Buhari ve PDP’den Atiku Abubakar) Twitter üzerindeki siyasi mesajlarının, yaygın medyadaki haber gündemini nasıl belirlediklerini, gündem belirleme, gündem yaratma ve hipotez çerçeveleri kullanarak incelendi. Buna ek olarak, toplumun Nijerya 2019 Seçim Kampanyası sürecindeki siyasi konular hakkındaki algısının söz konusu süreçte nasıl etkilendiği incelenmektedir. Adı geçen adayların Twitter’da paylaştığı n300 tweet ve Daily Trust, Punch ve Vanguard Gazeteleri’nin paylaştığı n300 haber içerikli Twitter paylaşımı hem nicel hem de nitel çözümleme metotları ile incelenmektedir. Söz konusu çalışma, adayların seçim kampanyaları kapsamında gerçekleştirdikleri etkinlikler içerisinde en başta yer alan kaynaklardan birinin Twitter paylaşımları olduğunu ortaya koymaktadır. Dolayısıyla, her iki politikacının gündemlerinde ve seçim süreci boyunca yaygın medyanın haber gündemlerinde benzer yöntemlerle paylaşımlar yapma eğiliminin baskın olduğu bulunmuştur. Ayrıca, adayların haberlerdeki Twitter paylaşımlarının sunulma şeklinin, adayların gündemlerinin anlaşılması konusunda olumlu yönde bir vurgu yarattığı gözlemlenmektedir. Söz konusu çalışma, gazeteciler ve medya açısından gelişmiş profesyonellik ihtiyacının var olduğunu ve Nijeryalı kitlenin medya okuryazarlığı becerilerinin geliştirilmesi gerektiği gerçeğini de ortaya koymaktadır.
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2019. Supervisor: Assoc. Prof. Dr. Metin Ersoy.
Keywords: Communication and Media Studies Department; Mass Media and Peace--Peace Journalism; Agenda-Building; Agenda-Setting; Framing; Mainstream Media; Nigeria; Participatory Media; Political News; Twitter